Implementation Pattern of CBT UKMPPD Public Health Tutoring at the Faculty of Medicine, Cenderawasih University - Labobar, Maryam Kathrien; Irab, Semuel Piter; Anggai, Martapina; Tingginehe, Rosmin Mariati; Togodly, Arius; Rantetoding, Septevanus (Formosa Journal of Science and Technology, 2024)
The aim of this research is to determine the implementation pattern of CBT Public Health Science tutoring for the Doctoral Professional Program Student Competency Test for medical students at Cenderawasih University, Jayapura. This research is a qualitative descriptive study with a total of 12 informants from the Faculty of Medicine, Uncen. The research results showed that the implementation of Public Health Tutoring had gone well but was not optimal due to the short implementation time. The Public Health Study Guidance Method required by students is the lecture method of providing material, learning modules and practice questions on the Student Competency Test for the Medical Professional Program. Tutoring student attendance tends to be low due to the long distance from home, untimely schedules and uncomfortable tutoring rooms. The very satisfactory Cumulative Achievement Index of tutoring students is not directly proportional to the low pretest-posttest of Public Health Tutoring and low Competency Test passing results.